(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
Between August and October 2019, the Amazon gained significant prominence in the press and on social media due to the fires ravaging the world’s largest tropical forest. The release of data by Brazilian National Institute for Space Research (INPE), which pointed to an increase in both fires and deforestation, negatively impacted the image of the Brazilian federal government (Bolsonaro Administration) regarding its environmental policies. In response, the government adopted retaliatory measures against INPE and other environmental protection agencies. Within this context, YouTube played a central role in the dissemination of (dis)information about environmental crimes in the Amazon and other biomes, becoming a battleground for actors seeking to influence public opinion and mark ideological positions. This study maps and analyzes the disinformation network about the Amazon that emerged on YouTube between August and October 2019, as well as the strategies used by disinformation agents. Using Controversy Mapping, the research identified the main actors involved in the debate about the Amazon and the arguments they advanced. The findings demonstrate that disinformation was used as a rhetorical weapon by far-right channels aligned with the Bolsonaro government, aiming to protect the government’s image and to weaken environmental protection institutions and legislation. The study also found that disinformation occupied a predominant space among the most viewed videos, indicating that YouTube’s lack of regulation and content moderation policies have been ineffective in curbing the spread of false information on the platform.